The Duty to Join Forces: When Individuals Lack Control. (9th March 2019) - Hindriks, Frank
Abstract: Some harms are such that they cannot be prevented by a single individual because she lacks the requisite control. Because of this, no individual has the obligation to do so. It may be, however, that the harm can be prevented when several individuals combine their efforts. I argue that in many such situations each individual has a duty to join forces: to approach others, convince them to contribute, and subsequently make a coordinated effort to prevent the harm. A distinctive feature of this proposal is that, in the first instance, it focuses on mobilizing others rather than on preventing the outcome. As it ultimately concerns a collective harm, the duty to join forces is irreducibly collective. Furthermore, once enough people have been mobilized, they have a collective obligation to prevent the harm that is irreducibly collective also because it applies to the collective as such.